Ring Opening by Hydrogen Peroxide in Alkaline Solution - MARJANI, K.; ASHOURI, A.; ARAZI, O.; ALIZADEH, H. (Asian Journal of Chemistry, 2010)
3,4-Diphenyl-4-hydroxy-2-cyclopentene-1-one (1) and 3,4-diphenyl- 2-cyclopentene-1-one (2) give epoxides, but ketols (3-22) produce benzoic acid and its derivatives with hydrogen peroxide in alkaline solution.